2023
DOI: 10.1108/jpif-10-2021-0084
|View full text |Cite
|
Sign up to set email alerts
|

Improving the benchmarking of ESG in real estate investment

Abstract: Purpose Environment, social, governance (ESG) has taken on increased importance in real estate investment in recent years, with benchmarking ESG being critically important for more informed real estate investment decision-making. Using 60 stakeholder interviews with senior real estate executives, this paper examines the strategic issues regarding benchmarking ESG in real estate investment; specifically, identifying areas going forward where ESG benchmarks need to be improved. This includes the issues of granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Plate 1 provides some examples of these sources of renewable energy infrastructure. With real estate being a significant contributor to global carbon emissions, this also takes on increased importance in the real estate space at an individual property-level and at a broader real estate portfolio-level, as real estate players address the issues of mitigating climate change risk in their portfolios (Newell et al ., 2023).…”
Section: Significance Of Renewable Energy Infrastructurementioning
confidence: 99%
“…Plate 1 provides some examples of these sources of renewable energy infrastructure. With real estate being a significant contributor to global carbon emissions, this also takes on increased importance in the real estate space at an individual property-level and at a broader real estate portfolio-level, as real estate players address the issues of mitigating climate change risk in their portfolios (Newell et al ., 2023).…”
Section: Significance Of Renewable Energy Infrastructurementioning
confidence: 99%
“…Meanwhile, Renigier-Biłozor et al [23] observed reluctance to accept modern automated tools for property valuation from traditional property appraisers, and stressed the importance of such solutions for overall sustainable development. Newell et al [182] also highlighted the need to improve the use of Environment, Social, and Governance (ESG) benchmarking, with emphasis on the climate risks in different regions. Post-pandemic, more research has explored the application of data analytics, from combining spatial and temporal evolution using context-aware matrix factorization to understand regional markets [183], to using Chain-of-thought (COT) prompt engineering in generating property valuation reports [184].…”
Section: Practical and Managerial Implicationsmentioning
confidence: 99%
“…Regulators have begun to evaluate their possibilities to limit the power demand of these bitcoin networks in light of the current climate catastrophe and global energy crises [18]. Furthermore, businesses are increasingly focusing on sustainable business practices in compliance with ESG requirements [19,20]. Therefore, one can argue that, from a business side, the development of energy-efficient blockchain solutions may be incentivized.…”
Section: Operating Modelmentioning
confidence: 99%